Law Enforcement Against Drug Abuse in Society : Implementation of Indonesian Law Number 35 of 2009 on Narcotics - Yuanita Mayangsari; Noenik Soekorini; Vieta Imelda Cornelis (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Drug abuse constitutes a serious threat to public health, social stability, and national security. This study examines law enforcement mechanisms against drug abuse under Indonesian Law Number 35 of 2009 on Narcotics and evaluates preventive measures implemented to combat this phenomenon. Employing a normative juridical approach through a comprehensive literature review, this research analyses the implementation of both penal and non-penal approaches in addressing narcotics-related offences. The findings reveal that law enforcement practices predominantly emphasise punitive measures, despite legislative provisions accommodating rehabilitation for drug users. The dual approach integrating criminal sanctions with social and health services remains suboptimal due to institutional constraints, limited rehabilitation facilities, inadequate training for law enforcement personnel, and weak inter-agency coordination. Preventive efforts through education, family empowerment, school-based programs, community engagement, and media campaigns have been implemented but continue to face challenges, including social stigma and insufficient public awareness. This study recommends strengthening restorative justice implementation, expanding rehabilitation service capacity, and enhancing cross-sectoral collaboration to build societal resilience against drug abuse while ensuring that users receive appropriate treatment rather than mere criminalisation.